The Effect of Different Hydroponic Nutrient Sources on Bok Choy Plant Growth (Brassica rapa L.) - Sabar, Muhammad; Muliana, Muliana; Khusrizal, Khusrizal; Yusra, Yusra; Baidhawi, Baidhawi (Journal of Tropical Horticulture, 2022)
Hydroponic cultivation of bok choy is an alternative that can be done to increase plant production during the increase of limited land conditions. The use of nutrients is one of the determinants of the success of hydroponic cultivation. Cow urine, shallot extract, coconut water, AB Mix nutrients, and NPK fertilizer are sources of nutrients that can be used as they are easy to obtain and have a good effect on the growth of bok choy. The research started from September 2020 - September 2021 and used a non-factorial Completely Randomized Design (CRD) with 3 replications so that 15 experimental units were obtained. The treatments were: N0 (aquades = 100% (1 liter), N1 (Cow Urine = 3% (30 ml/liter), N2 (Shallot Extract = 4% (40 g/liter), N3 (Coconut Water = 30 % (300 ml/liter), N4 (Nutrition AB Mix = 1% (10 ml/liter), N5 (15: 15 : 15 NPK Fertilizer = 0.12% (1.2 g/liter).